Partographic analysis of labour by modified who partograph in primigravidae: a prospective observational study - Pujar, Kavitha G.; Salian, Shruthi V.; Kulkarni, Sunanda R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective of this study was to assess the role of partogram in the analysis of outcome of spontaneous labour in primigravidae at term with singleton pregnancy with vertex presentation. Methods: This prospective observational study was carried out in Chinmaya Mission Hospital, Bangalore over a period of 2 years, from February 2013 to March 2015. A partographic analysis of labour was done in 300 primigravidae using modified WHO partogram. The study population was divided into 3 groups, group I- cervical dilatation and descent curve falling to the left of alert line. Group II- cervical dilatation and descent curve falling to the right of alert line. Group III cervical dilatation and descent curve falling to the right of action line. Partographic analysis was done and maternal and neonatal outcomes were studied in these groups. Results: In this study, 300 primigravidae in labour were analysed. Of these 282(94%) women belonged to group I, 18(6%) belonged to group II. There were no cases in group III. Mean durations of active phases of labour were 4.75 hrs and 7.74 hrs in group I and II. In group I, 275(98%) women delivered vaginally, 7(2%) underwent LSCS and 96 (34%) had instrumental deliveries. In group II, 14(78%) women delivered vaginally, 4(23%) had instrumental delivery and 4(22%) underwent LSCS. Conclusions: The WHO modified partogram is highly effective in reducing both maternal and neonatal morbidity. It aids in assessing the progress of labour and to identify when intervention is necessary.